2010
DOI: 10.1111/j.1741-6787.2009.00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Nurse Specialists' Approaches in Selecting and Using Evidence to Improve Practice

Abstract: This study indicates that although CNSs select and use evidence from a wide variety of sources, further development of their capacity to retrieve and transfer knowledge may increase the uptake of research findings in nursing practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 53 publications
1
45
0
Order By: Relevance
“…This key element of the role is found across countries in the majority of studies on clinical specialists 29,44,45 and APs 46 and, when practiced with clinical expertise and in line with clients' preferences, demonstrates ''best practice.'' 47 The same amount of EBP did not appear in nonYpost-holding sites, indicating that clinicians, in various health professions, did not perform to the same level as CS/APs, perhaps because of a lack of clear role position descriptions and expectations to fulfill such responsibilities.…”
Section: Discussionmentioning
confidence: 97%
“…This key element of the role is found across countries in the majority of studies on clinical specialists 29,44,45 and APs 46 and, when practiced with clinical expertise and in line with clients' preferences, demonstrates ''best practice.'' 47 The same amount of EBP did not appear in nonYpost-holding sites, indicating that clinicians, in various health professions, did not perform to the same level as CS/APs, perhaps because of a lack of clear role position descriptions and expectations to fulfill such responsibilities.…”
Section: Discussionmentioning
confidence: 97%
“…A study by J. Profetto-McGrath carried out among Canadian departmental nurses showed that major obstacles in using EBNP in their everyday clinical practice included a lack of time and appropriate sources of scientific information as well as organizational difficulties [24]. This was also confirmed by our study performed among both groups of nurses who added the following obstacles: unfamiliarity with the principles of methodology of conducting research and components of research studies as well as ignorance of statistics, limited access to up-to-date scientific evidence and scientific publications for nurses.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier survey of APNs Gerrish et al (2011) identified that expertise in EBP is variable, with those possessing a master's degree being more confident than those with lower academic qualifications. Profetto-McGrath et al (2010) also identified the need for further development of APNs capacity to retrieve and transfer knowledge in order to increase the uptake of research findings into nursing practice. Educational preparation needs to enable APNs to develop the knowledge and skills to provide evidence-based care themselves, as well as develop skills in different strategies deemed to be effective in promoting EBP among their colleagues.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…The aim of this study was to explore their impact in promoting EBP amongst FLNs. Goudreau (2007) and Profetto-McGrath et al (2010) assert that APNs are well equipped to help FLNs implement evidence-based change. Although it is widely 3 acknowledged that APNs have key role in promoting EBP (Davies et al 2006) among FLNs there is a paucity of research examining how APNs fulfil this expectation and what impact their influence may have.…”
Section: Introductionmentioning
confidence: 99%